Influence of protected environments and irrigation methods on plant growth and seed yield of coriander (Coriandrum sativum) - G LAL; BALRAJ SINGH; S P MAHERIA (The Indian Journal of Agricultural Sciences, 2015)
A field experiment to study the effect of different protected environments and irrigation methods on growth and yield of coriander (Coriandrum sativum L.) was conducted at NRCSS, Tabiji, Ajmer, Rajasthan during rabi season of the year 2008-09 to 2010-11. The experiment comprising four treatments of protected environments, viz. plastic covered walk in tunnel, insect proof net covered walk in tunnel, shade net covered walk in tunnel, plastic low tunnel and control (open conditions) in main plots and three irrigation method treatments (pressurized drip irrigation, low pressure drip irrigation and surface irrigation) in subplots was conducted with three replications in split plot design. The soil of the experimental plot was sandy loam, with low organic carbon and nitrogen, medium in available phosphorus and sufficient in available potassium. Impact of protected environment and methods of irrigation was recorded with respect to plant growth, yield attributes and seed yield. The plastic covered walk in tunnel protection resulted highest plant height, maximum branches/plant at harvest, maximum number of umbels/plant, maximum number of seeds/umbel and highest seed yield. Among irrigation methods, low pressure drip irrigation exhibited significantly higher plant height at 60 days after sowing (DAS) as well as at harvest with maximum number of umbels per plant, maximum number of umbellates/umbel and maximum seed yield. On the basis of above study it is concluded that plastic covered walk in tunnel with low pressure drip method of irrigation is best for realizing better plant growth and seed yield of coriander as compared to all other treatments.